p Pemanfaatan Marketplace dalam Pengembangan Bisnis Kuliner pada Kelurahan Mappasiale Kabupaten PANGKEP - Asmawaty Azis Asma; Andita Dani Achmad; Kurniawan Harun Rasyid; Muhammad Taufik; Amika Sapan (JOURNAL OF TRAINING AND COMMUNITY SERVICE ADPERTISI (JTCSA), 2022)
The culinary business in the Mappasiale Village, Pangkajene District has not yet utilized a digital platform so that the culinary business in this village is not yet known by many people. By utilizing the marketplace, it is possible for businesses to have additional channels to sell their products because the marketplace users continue to increase, do not require large capital, easy transaction processes, and can monitor business growth so that culinary businesses in Mappasiale Village can expand their market reach. The form of ADPERTISI PKM activities in Mappasiale Village is the method of presentation and discussion between the ADPERTISI team and the community in Mappasiale Village, Pangkajene District, PANGKEP Regency.